2022
DOI: 10.3390/app12042107
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Temperatures on Polyphenols during Extraction

Abstract: Background: Polyphenols are a set of bioactive compounds commonly found in plants. These compounds are of great interest, as they have shown high antioxidant power and are correlated to many health benefits. Hence, traditional methods of extraction such as solvent extraction, Soxhlet extraction and novel extraction technologies such as ultrasound-assisted extraction and subcritical water extraction (SWE) have been investigated for the extraction of polyphenols. Scope and Approach: Generally, for traditional ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
107
2
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 219 publications
(114 citation statements)
references
References 89 publications
4
107
2
1
Order By: Relevance
“…This information was in accordance with previous studies of natural compounds that have investigated the effect of drying temperatures in the antioxidant activity of grape pomace peels extracts. The authors have found that the antioxidant activity at 120 °C was lower (1.7 times) than that obtained at 20 °C [ 27 , 28 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This information was in accordance with previous studies of natural compounds that have investigated the effect of drying temperatures in the antioxidant activity of grape pomace peels extracts. The authors have found that the antioxidant activity at 120 °C was lower (1.7 times) than that obtained at 20 °C [ 27 , 28 ].…”
Section: Resultsmentioning
confidence: 99%
“…This antioxidant power would be due to their bioactive content, such as polyphenols, since several research have reported that spices and herbs, with high phenolic content, are excellent sources of natural antioxidant compounds [ 30 ]. Nevertheless, the relationship between the structure of polyphenols and their antioxidant power is not yet well known [ 28 ]. Therefore, saffron floral by-products could be a source of natural antioxidants resulting from the saffron spice handling and processing and can be used to develop nutraceutical or functional food products with positive effects in human health such as the protection against oxidative stress [ 31 ].…”
Section: Resultsmentioning
confidence: 99%
“…Since the temperature in the P-DSC was much higher than in the Rancimat method, the values obtained were lower. It is known that temperature in particular can have a decisive impact on the stability of phenolic substances and can result in a decrease in antioxidative effect [83]. In some cases, a decrease in antioxidant activity was found even at temperatures of 40 and 60 °C, while in other studies, a decrease was found only at higher temperatures of 100 and 120 °C [83][84][85][86][87][88].…”
Section: Analysis Of Oil Stabilitymentioning
confidence: 96%
“…It is known that temperature in particular can have a decisive impact on the stability of phenolic substances and can result in a decrease in antioxidative effect [83]. In some cases, a decrease in antioxidant activity was found even at temperatures of 40 and 60 °C, while in other studies, a decrease was found only at higher temperatures of 100 and 120 °C [83][84][85][86][87][88]. Thereby, the type of phenolic compounds determines the influence of the temperature.…”
Section: Analysis Of Oil Stabilitymentioning
confidence: 98%
See 1 more Smart Citation